Democratic vernaculars - Sproule, J. Michael, 1949- author.
1 online resource
Keywords: "Democratic Vernaculars is a comprehensive, culturally inclusive, and thematically unified history of the communicative, audience-centered rhetorical vernacular that occupies the "middle range" of English, bounded on the one side by expressive structure (grammar and linguistics) and on the other by aesthetics (literature). Broadening the history of rhetoric by considering a vast collection of vernacular resources such as elementary grammars and readers, popular guidebooks, textbooks, and rhetorical treatises, this book advances the history of rhetorical theory and pedagogy since the 17th century by examining ways in which diverse vectors of rhetorical vernacular coalesced to produce an English language sufficiently idiomatic for practical social exchange while being, at the same time, suitable for higher literary, scholarly, and cultural pursuits. Democratic Vernaculars is essential reading for scholars in rhetoric and the histories of language and education, and can serve as a text for upper-division undergraduate and graduate courses in rhetoric"--